Lipid metabolism in myeloid cell function and chronic inflammatory diseases - Ito, Ayaka; Suganami, Takayoshi (Frontiers in Immunology, 2025)
Immune cells adapt their metabolism in response to their differentiation and activation status to meet the energy demands for an appropriate immune response. Recent studies have elucidated that during immune cell metabolic reprogramming, lipid metabolism, including lipid uptake, de novo lipid synthesis and fatty acid oxidation, undergoes significant alteration, resulting in dynamic changes in the quantity and quality of intracellular lipids. Given that lipids serve as an energy source and structural components of cellular membranes, they have important implications for physiological function. Myeloid cells, which are essential in bridging innate and adaptive immunity, are sensitive to these changes. Dysregulation of lipid metabolism in myeloid cells can result in immune dysfunction, chronic inflammation and impaired resolution of inflammation. Understanding the mechanism by which lipids regulate immune cell function might provide novel therapeutic insights into chronic inflammatory diseases, including metabolic diseases, autoimmune diseases and cancer. (143 words)